An exposition to the understanding of liberalism - Sulaiman, Kabuye Uthman (SAS Publishers (Scholars Academic and Scientific Publishers) A Unit of Scholars Academic and Scientific Society, India, 2018)
What is liberalism? In what ways does liberalism differ from conservatism? These are important and interesting questions, worthy of further discussions. This paper addressed the first question; it described liberalism as a secular worldview in two sections. Section one delineated the meaning, history and objective of liberalism. Section two provided an elucidation of the values or principles of liberalism, namely, moral worth of individuals, private property and limited government. Both liberalism and conservatism aim to promote a good life for individuals but they differ in their conceptions of a good life. The earmark of liberalism is that individual autonomy is the basis of a good life. Moreover, conservatives believe that social authority is key to a good life. Much of this study has focused on autonomy. It is made clear that autonomy is a condition of being legislated by reason. Opposed to autonomy is heteronomy, i.e. a condition of being legislated by God. The study has contended that liberalism is a secular worldview because: (1) it detaches individuals from the Holy Scriptures or spiritual sources, and (2) it places man over God and reason over revelation. This work is intended to serve as a basis for evaluating liberal Islam which will be undertaken in my next work entitled Understanding the Islamic Worldview. It is hoped that this study will deepen the understanding of liberalism as a secular worldview.